Efficacy and Safety of Adalimumab in Pediatric Ulcerative Colitis: A Real-life Experience from the SIGENP-IBD Registry. - Aloi, Marina; Bramuzzo, Matteo; Arrigo, Serena; Romano, Claudio; D'Arcangelo, Giulia; Lacorte, Doriana; Gatti, Simona; Illiceto, Maria T; Zucconi, Francesca; Dilillo, Dario; Zuin, Giovanna; Knafelz, Daniela; et al. (J Pediatr Gastroenterol Nutr, 2018)
OBJECTIVES: The aim of this study was to evaluate the effectiveness and safety of adalimumab (ADA) in children with ulcerative colitis (UC) previously treated with infliximab (IFX). METHODS: Retrospective study including children with UC from a national registry who received ADA therapy. The primary endpoint was the rate of corticosteroid-free remission at week 52. Secondary outcomes were the rate of sustained clinical remission, primary nonresponse, and loss of response at weeks 12, 30, and 52 and rate of mucosal healing and side effects at week 52. RESULTS: Thirty-two children received ADA (median age 10 ± 4 years). Median disease duration before ADA therapy was 27 months. All patients received previous IFX (43% intolerant, 50% nonresponders [37.5% primary, 42.5% secondary nonresponders], 6.7% positive anti-IFX antibodies). Fifty-two weeks after ADA initiation, 13 patients (41%) were in corticosteroid-free remission. Mucosal healing occurred in 9 patients (28%) at 52 weeks. The cumulative probability of a clinical relapse-free course was 69%, 59%, and 53% at 12, 30, and 52 weeks, respectively. Ten patients (31%) had a primary failure and 5 (15%) a loss of response to ADA. No significant differences in efficacy were reported between not-responders and intolerant to IFX (P = 1.0). Overall, 19 patient (59%) maintained ADA during 52-week follow-up. Seven patients (22%) experienced an adverse event, no serious side effects were observed and none resulted in ADA discontinuation. CONCLUSIONS: Based on our data, ADA seems to be effective in children with UC, allowing to recover a significant percentage of patients intolerant or not-responding to IFX. The safety profile was good.

Multicentric Case-Control Study on Azathioprine Dose and Pharmacokinetics in Early-onset Pediatric Inflammatory Bowel Disease. - Stocco, Gabriele; Martelossi, Stefano; Arrigo, Serena; Barabino, Arrigo; Aloi, Marina; Martinelli, Massimo; Miele, Erasmo; Knafelz, Daniela; Romano, Claudio; Naviglio, Samuele; Favretto, Diego; Cuzzoni, Eva; et al. (Inflamm Bowel Dis, 2017)
BACKGROUND: Early-onset inflammatory bowel disease (IBD) is generally aggressive, with a high probability of complications and need of surgery. Despite the introduction of highly effective biological drugs, treatment with azathioprine continues to be important even for early-onset IBD; however, in these patients azathioprine response seems to be reduced. This study evaluated azathioprine doses, metabolite concentrations, and their associations with patients' age in children with IBD treated at 6 tertiary pediatric referral centers. METHODS: Azathioprine doses, metabolites, and clinical effects were assessed after at least 3 months of therapy in 17 early-onset (age < 6 yr, cases) and 51 nonearly-onset (aged > 12 and <18 yrs, controls) patients with IBD. Azathioprine dose was titrated on therapeutic efficacy (response and adverse effects). Azathioprine metabolites and thiopurine methyltransferase activity were determined by high-performance liquid chromatography with ultra violet-vis detection (HPLC-UV) methods. RESULTS: Frequency of patients in remission was similar among early-onset and control groups, respectively (82% and 84%, P value = 0.72). Early-onset patients required higher doses of azathioprine (median 2.7 versus 2.0 mg·kg·d, P value = 1.1 × 10). Different doses resulted in comparable azathioprine active thioguanine nucleotide metabolite concentrations (median 263 versus 366 pmol/8 × 10 erythrocytes, P value = 0.41) and methylmercaptopurine nucleotide concentrations (median 1455 versus 1532 pmol/8 × 10 erythrocytes, P value = 0.60). Lower ratios between thioguanine nucleotide metabolites and azathioprine doses were found in early-onset patients (median 98 versus 184 pmol/8 × 10 erythrocytes·mg·kg·d, P value = 0.017). Interestingly, early-onset patients presented also higher thiopurine methyltransferase activity (median 476 versus 350 nmol methylmercaptopurine/mg hemoglobin/h, P-value = 0.046). CONCLUSIONS: This study demonstrated that patients with early-onset IBD present increased inactivating azathioprine metabolism, likely because of elevated activity of the enzyme thiopurine methyltransferase.
Keywords: Adolescent; Age of Onset; Antimetabolites; Azathioprine; Case-Control Studies; Child; Child, Preschool; Chromatography, High Pressure Liquid; Dose-Response Relationship, Drug; Erythrocytes; Female; Guanine Nucleotides; Humans; Inflammatory Bowel Diseases; Male; Mercaptopurine; Methyltransferases; Thioguanine

Pediatric gastrointestinal bleeding: Perspectives from the Italian Society of Pediatric Gastroenterology. - Romano, Claudio; Oliva, Salvatore; Martellossi, Stefano; Miele, Erasmo; Arrigo, Serena; Graziani, Maria Giovanna; Cardile, Sabrina; Gaiani, Federica; de'Angelis, Gian Luigi; Torroni, Filippo (World J Gastroenterol, 2017)
There are many causes of gastrointestinal bleeding (GIB) in children, and this condition is not rare, having a reported incidence of 6.4%. Causes vary with age, but show considerable overlap; moreover, while many of the causes in the pediatric population are similar to those in adults, some lesions are unique to children. The diagnostic approach for pediatric GIB includes definition of the etiology, localization of the bleeding site and determination of the severity of bleeding; timely and accurate diagnosis is necessary to reduce morbidity and mortality. To assist medical care providers in the evaluation and management of children with GIB, the "Gastro-Ped Bleed Team" of the Italian Society of Pediatric Gastroenterology, Hepatology and Nutrition (SIGENP) carried out a systematic search on MEDLINE PubMed (http://www.ncbi.nlm.nih.gov/pubmed/) to identify all articles published in English from January 1990 to 2016; the following key words were used to conduct the electronic search: "upper GIB" and "pediatric" [all fields]; "lower GIB" and "pediatric" [all fields]; "obscure GIB" and "pediatric" [all fields]; "GIB" and "endoscopy" [all fields]; "GIB" and "therapy" [all fields]. The identified publications included articles describing randomized controlled trials, reviews, case reports, cohort studies, case-control studies and observational studies. References from the pertinent articles were also reviewed. This paper expresses a position statement of SIGENP that can have an immediate impact on clinical practice and for which sufficient evidence is not available in literature. The experts participating in this effort were selected according to their expertise and professional qualifications.
Keywords: Adolescent; Child; Child, Preschool; Diagnostic Imaging; Endoscopy; Gastroenterology; Gastrointestinal Diseases; Gastrointestinal Hemorrhage; Hemodynamics; Humans; Infant; Infant, Newborn; Italy; Pediatrics; Recurrence; Societies, Medical

Effect of Early Versus Late Azathioprine Therapy in Pediatric Ulcerative Colitis. - Aloi, Marina; DʼArcangelo, Giulia; Bramuzzo, Matteo; Gasparetto, Marco; Martinelli, Massimo; Alvisi, Patrizia; Illiceto, Maria Teresa; Valenti, Simona; Distante, Manuela; Pellegrino, Salvatore; Gatti, Simona; Arrigo, Serena; et al. (Inflamm Bowel Dis, 2016)
BACKGROUND: We aimed at describing the efficacy of azathioprine (AZA) in pediatric ulcerative colitis, comparing the outcomes of early (0-6 months) versus late (6-24 months) initiation of therapy. METHODS: Children with ulcerative colitis treated with AZA within 24 months of diagnosis were included. Corticosteroid (CS)-free remission and mucosal healing (MH), assessed by endoscopy or fecal calprotectin, at 12 months were the primary outcomes. Patients were also compared for CS-free remission and MH, need for treatment escalation or surgery, number of hospitalizations, and adverse events during a 24-month follow-up. RESULTS: A total of 121 children entered the study (median age 10.5 ± 4.0 years, 59% girls). Seventy-six (63%) started AZA between 0 and 6 months (early group) and 45 (37%) started between 6 and 24 months (late group). Seventy-five percent and 53% of patients in the early and late group, respectively, received CS at the diagnosis (P = 0.01). CS-free remission at 1 year was achieved by 30 (50%) of the early and 23 (57%) of the late patients (P = 0.54). MH occurred in 37 (37%) patients at 1 year, with no difference between the 2 groups (33% early, 42% late; P = 0.56). No difference was found for the other outcomes. CONCLUSIONS: Introduction of AZA within 6 months of diagnosis seems not more effective than later treatment to achieve CS-free remission in pediatric ulcerative colitis. MH does not depend on the timing of AZA initiation; however, because of the incomplete comparability of the 2 groups at the diagnosis and the use of fecal calprotectin as a surrogate marker of MH, our results should be further confirmed by prospective studies.

The diagnostic challenge of very early-onset enterocolitis in an infant with XIAP deficiency. - Girardelli, Martina; Arrigo, Serena; Barabino, Arrigo; Loganes, Claudia; Morreale, Giuseppe; Crovella, Sergio; Tommasini, Alberto; Bianco, Anna Monica (BMC Pediatr, 2015)
BACKGROUND: Aggressive course and resistance to treatments usually characterize very early onset inflammatory bowel disease (VEO-IBD). Some VEO-IBD cases are due to monogenic immune defects and can benefit from hematopoietic stem cell transplantation (HSCT). CASE PRESENTATION: We describe a Caucasian male baby who presented in the first months of life macrophage activation syndrome, followed by intractable colitis, recurrent episodes of fever and mild splenomegaly. After several immunological, genetic and clinical investigations, subsequently a therapeutic attempt with colectomy, analysis of VEO-IBD-associated genes, revealed a causative mutation in XIAP. The genetic diagnosis of a primary immune deficiency allowed curing the boy with hematopoietic stem cell transplantation. CONCLUSION: Our report, together with novel findings from recent literature, should contribute to increase awareness of monogenic immune defects as a cause of VEO-IBD. Comprehensive genetic analysis can allow a prompt diagnosis, resulting in the choice of effective treatments and sparing useless and damaging procedures.

Effect of Thalidomide on Clinical Remission in Children and Adolescents with Ulcerative Colitis Refractory to Other Immunosuppressives: Pilot Randomized Clinical Trial. - Lazzerini, Marzia; Martelossi, Stefano; Magazzù, Giuseppe; Pellegrino, Salvatore; Lucanto, Maria Cristina; Barabino, Arrigo; Calvi, Angela; Arrigo, Serena; Lionetti, Paolo; Lorusso, Monica; Mangiantini, Francesca; Fontana, Massimo; et al. (Inflamm Bowel Dis, 2015)
BACKGROUND: In a randomized controlled trial, thalidomide has shown to be effective in refractory Crohn's disease in children. This pilot study aimed at evaluating thalidomide in refractory pediatric ulcerative colitis (UC). METHODS: Double-blind, placebo-controlled randomized clinical trial on thalidomide 1.5 to 2.5 mg/kg/day in children with active UC despite multiple immunosuppressive treatments. In an open-label extension, nonresponders to placebo received thalidomide for an additional 8 weeks; all responders were followed up for a minimum of 52 weeks. RESULTS: Twenty-six children with refractory UC were randomized to thalidomide or placebo. Clinical remission at week 8 was achieved by significantly more children treated with thalidomide {10/12 (83.3%) versus 2/11 (18.8%); risk ratio, 4.5 (95% confidence interval [CI], 1.2-16.4); P = 0.005; number needed to treat, 1.5}. Of the nonresponders to placebo who were switched to thalidomide, 8 of 11 (72.7%) subsequently reached remission at week 8 (risk ratio, 4.0 [95% CI, 1.1-14.7]; number needed to treat, 2.45; P = 0.01). Clinical remission in the thalidomide group was 135.0 weeks (95% CI, 32-238), compared with 8.0 weeks (95% CI, 2.4-13.6) in the placebo group (P < 0.0001). Cumulative incidence of severe adverse events was 3.1 per 1000 patient-weeks. Peripheral neuropathy and amenorrhea were the most frequent adverse events. CONCLUSIONS: In this pilot randomized controlled trial on cases of UC refractory to immunosuppressive therapy, thalidomide compared with placebo resulted in improved clinical remission at 8 weeks of treatment and in longer term maintenance of remission. These findings require replication in larger clinical studies evaluating both thalidomide efficacy and safety.

Severe inflammatory bowel disease associated with congenital alteration of transforming growth factor beta signaling. - Naviglio, Samuele; Arrigo, Serena; Martelossi, Stefano; Villanacci, Vincenzo; Tommasini, Alberto; Loganes, Claudia; Fabretto, Antonella; Vignola, Silvia; Lonardi, Silvia; Ventura, Alessandro (J Crohns Colitis, 2014)
Transforming growth factor beta is a pleiotropic cytokine which plays a central role in the homeostasis of the immune system. A complex dysregulation of its signaling occurs in Loeys-Dietz syndrome, a monogenic disorder caused by mutations of transforming growth factor beta receptors type 1 or type 2, characterized by skeletal involvement, craniofacial abnormalities, and arterial tortuosity with a strong predisposition for aneurysm and dissection. In addition, several immunologic abnormalities have been described in these patients, including an increased risk of allergic disorders as well as eosinophilic gastrointestinal disorders. The occurrence of inflammatory bowel disorders has been also reported, but it is poorly documented. We describe two unrelated children with Loeys-Dietz syndrome affected by severe chronic inflammatory colitis appearing at an early age. The intestinal disease presented similar features in both patients, including a histopathological picture of non-eosinophilic chronic ulcerative colitis, striking elevation of inflammatory markers, and a distinctly severe clinical course leading to failure to thrive, with resistance to multiple immunosuppressive treatments. One of the patients also presented autoimmune thyroiditis. Our report confirms that chronic ulcerative colitis may be associated with Loeys-Dietz syndrome. This finding suggests that an alteration of transforming growth factor beta signaling may by itself predispose to inflammatory colitis in humans, and represent an invaluable model to understand inflammatory bowel diseases.
Keywords: Child, Preschool; Colon; Colonoscopy; Female; Humans; Infant; Inflammatory Bowel Diseases; Loeys-Dietz Syndrome; Male; Signal Transduction; Transforming Growth Factor beta